2001
DOI: 10.1007/s002130100852
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that mesoaccumbens dopamine and locomotor responses to nicotine in the rat are influenced by pretreatment dose and strain

Abstract: Sensitisation of the mesoaccumbens dopamine response to nicotine is influenced by pre-treatment dose and the strain of rats used. It is not related directly to the expression of sensitised locomotor responses to the drug and, therefore, may be implicated in other psychopharmacological properties of the drug, including dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 23 publications
5
41
0
1
Order By: Relevance
“…In agreement with previous studies from our laboratory and others [19,83,84], nicotine increased the release of DA. This increase is consistent with enhanced activity of the DAergic system, effects that were decreased by pretreatment with NT69L.…”
Section: Effect Of Nt69l On Nicotine-and Alcohol-induced Biochemical supporting
confidence: 93%
“…In agreement with previous studies from our laboratory and others [19,83,84], nicotine increased the release of DA. This increase is consistent with enhanced activity of the DAergic system, effects that were decreased by pretreatment with NT69L.…”
Section: Effect Of Nt69l On Nicotine-and Alcohol-induced Biochemical supporting
confidence: 93%
“…Although nicotine-mediated DARPP32 activation was not observed in the NAc in the current work, this may have resulted from tissue sampling that did not distinguish between core and shell subregions. Because DARPP32 T34 phosphorylation occurs downstream of dopamine D 1 receptor activation (Greengard et al, 1999), and nicotine leads to sensitization of dopamine release in the core and not the shell (Iyaniwura et al, 2001), nicotinemediated DARPP32 activation would be more likely to occur in the NAc core. Thus, samples containing both NAc core and shell tissue may have diluted the effect of a core-specific increase in phosphorylated DARPP32.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the NAc is a heterogeneous region most often divided into two distinct anatomically and functionally different regions, that is the central core and the surrounding shell compartment [65][66][67][68][69] and it has been suggested that dopaminergic innervation of the NAc core is associated with the nigrostriatal system, while that of the NAc shell is related to the mesolimbic system [70]. Alcohol has been shown to increase the release of dopamine in NAc shell, but not in the core [71][72][73]. Studies are also emerging suggesting the need for further division of this brain region since it was demonstrated that a borderline region between the core and shell of the NAc is the region most responsive to alcohol [74].…”
Section: Preclinical Evidence: Acute Alcohol Exposure and Dopaminementioning
confidence: 99%